A Study on the Collaborative Governance Mechanism for Electricity Aggregators Involving Multiple Stakeholders: A Perspective Based on Stakeholder Theory - Yingjie Xiong; Hongmei Ma (Economics and Public Policy, 2026)
As platform-based market entities that integrate distributed resources within the new power system, electricity aggregators have become a key enabler for achieving high-proportion renewable energy grid integration and flexible demand-side regulation. However, issues such as disputes over revenue distribution and high resource exit rates, which have emerged during their rapid development, stem from the heterogeneity of multiple stakeholders’ demands and power asymmetries. Existing research has focused excessively on technical optimisation and market mechanism design, whilst neglecting the governance essence of these entities.Drawing on the salience model within stakeholder theory, this paper identifies and classifies key stakeholders, including the government, grid operators, owners of distributed resources, and electricity consumers; combining this with collaborative governance theory, it analyses the causes of conflicting demands and the consequences of inefficient equilibria;thereby proposing a ‘Four-Dimensional Collaborative Governance Framework’ (comprising decision-making, incentive, risk-sharing and communication mechanisms) to achieve multi-stakeholder coordination through power redistribution, positive incentives and negative constraints, market-based risk diversification, and digital technologies such as blockchain.The empirical section takes Guangdong Province’s ‘Juhebao’ project as a case study. Through pre-post comparisons and horizontal benchmarking, it verifies that the implementation of this framework has yielded multiple Pareto improvements, including a 7.1 percentage point increase in the internal rate of return for resource owners, a 56 per cent rise in aggregators’ revenues, a reduction of 0.039 yuan/kWh in end-user electricity prices, and a decrease of nearly 13 percentage points in the resource exit rate.The study’s conclusions indicate that the four-dimensional framework is highly operational and universally applicable, providing an institutional model for the healthy and sustainable development of electricity aggregators nationwide. It also puts forward seven policy recommendations at the national, provincial and aggregator levels. This paper fills a gap in the theory and practice of multi-stakeholder collaborative governance for electricity aggregators, contributing a ‘Chinese solution’ to the development of a new electricity system.